“‘An effort to decide’: More Research into Kubrick’s Music Choices for 2001: A Space Odyssey” - McQuiston, Kate (Journal of Film Music, 2011)
This article supplies new information about Stanley Kubrick’s musical decision-making process on 2001: A Space Odyssey. This article draws on correspondence, anecdotal evidence, and legal documents housed in the Stanley Kubrick Archive, as well as the scholarly literature, to contribute new details to the timeline and nature of Kubrick’s provisional employment of Alex North and his selection process and pursuit of pre-existing works by György Ligeti. In addition, the article illuminates Kubrick’s ongoing search for the right music by listening to music – and having others listening to music with the film in mind, and his pursuit through legal channels, of recordings of pieces he wanted to use. In these efforts, he was guided by a desire to find works that would both fit the film and help generate profit.